In vitro susceptibility of clinical isolates of Brucella melitensis to fucidic acid - Celik, Ilhami; Cihangiroglu, Mustafa; Denk, Affan; Akbulut, Ayhan (Springer Japan, 2005)
Brucella species are facultative intracellular bacteria, and therefore a limited number of antibiotics are effective against these organisms. The side effects of drug combination schemes, and the incidences of relapses and therapeutic failures, have led to investigations of new drugs to treat brucellosis. The purpose of this study was to test the in vitro susceptibility of 50 Brucella melitensis isolates to fucidic acid, which has not previously been used for the treatment of brucellosis. The minimum inhibitory concentrations (MICs) of fucidic acid to 50 B. melitensis isolates that were obtained from blood and bone marrow cultures of patients with brucellosis were studied by the broth microdilution method. The MIC50 and MIC 90 values for the 50 B. melitensis strains' susceptibility to fucidic acid were determined to be 0.5 and 2 ?g/ml, respectively, and the MIC range was 0.125-2.0 ?g/ml. Further experiments are needed to reassess the activity of fucidic acid against intracellular Brucella spp. © Japanese Society of Chemotherapy and The Japanese Association for Infectious Diseases 2005.
Keywords: Brucella melitensis; Fucidic acid; Susceptibility